Influence of torque and bone type on stability quotient of two implant platforms: a clinical trial - Bannwart, Lisiane Cristina [UNESP]; Santos, Daniela Micheline dos [UNESP]; Souza, João Paulo do Vale [UNESP]; Melo Neto, Clóvis Lamartine de Moraes [UNESP]; Silva, Emily Vivianne Freitas da; Mazaro, José Vitor Quinelli [UNESP]; Salzedas, Leda Maria Piscinini [UNESP]; Goiato, Marcelo Coelho [UNESP] (FapUNIFESP (SciELO), 2024)
The objective of this study was to analyze the influence of insertion torque, bone type, and peri-implant bone loss on implant stability quotient (ISQ) of cylindrical external hexagon (EH) and Morse Taper (MT) implants. Forty-four single implants were placed in the edentulous areas of 20 patients who met the inclusion and exclusion criteria. Immediately after implant placement (t1) and after osseointegration (four and six months for mandible and maxilla, respectively) (t2), insertion torque, resonance frequency, and peri-implant bone loss were measured using probing depths and digital periapical radiography. A significant difference was noted in the ISQ values between t1 and t2 in type III bone for EH and MT implants. No significant difference in bone loss values was observed when comparing bone types for EH or MT in all evaluated sites. Based on marginal bone loss assessed using radiography, there was no significant difference between the MT and EH groups. A positive correlation between torque and ISQ t1 value was observed for MT (correlation: 0.439; p = 0.041) and EH (correlation: 0.461; p = 0.031) implants. For EH and MT implants, the greater the insertion torque, the greater was the ISQ value (moderately positive correlation). A weak negative correlation was found between bone type and ISQ t1 for MT implants. Contrarily, no correlation was observed between bone type and ISQ t1 for EH implants. In all cases, bone loss around the implants was clinically normal.